Women's Activism in Conflict Contexts: Beyond Mainstream Theoretical Approaches and Political Practices - Daniele, G. (CIEG International Congress "Gender Studies in Debate: Pathways, Challenges and Interdisciplinary Perspectives", 2016)
The paper I submit for your consideration is founded on the theoretical analysis and the fieldwork evaluation reported on in my Ph.D. dissertation, which has been published by Routledge in the form of a book entitled Women, Reconciliation and the Israeli-Palestinian Conflict: The Road Not Yet Taken. One of the main objectives of my research has been to analyse the most significant Palestinian and Israeli women’s political initiatives that have been influenced by and, in the majority of cases, prevented by obstacles associated with the Israeli military occupation in the last decade. Despite most of such women’s political proposals have been relegated to the margins of the mainstream arena, a few of them have succeeded in finding alternative politics and approaches that have assisted them in their struggles. In such a framework, by working with diverse discipline areas and research fields since the earliest stage of my academic career, my contribution is related to the current debate on gender studies dealing with academic theories and political practices in a perspective that could lead scholars and activists to seriously rethink the closer connection of their analytical approaches. This is a problematic issue not only in relation to the Israeli-Palestinian conflict, but also globally in further conflict contexts in the way it is concerned with the importance of understanding the variety of fissures within such studies, using conflicting narratives based on class, ethnicity, nationality, locality, gender, and age, by means of the intersectionality approach.